Public Administration, Competitiveness and Sustainable Development Proceedings of the National Conference organized by the Italian National Section of the IIAS. Trento, 23-24 May 2002 - Gregorio Arena (Proceedings e report, 2003)
The debate over the question of the sustainability of development has been for some time underway in relation to the environment and to public health. More recently attention has turned to other aspects of sustainability as well, now that a generally accepted meaning of the term has been reached which defines it as the sum total of policies for satisfying the needs of the present generation without compromising the capacity of future generations to satisfy their own needs. Within this broader context the role of public administration is obvious. One of the key questions that this volume has attempted to provide an answer is: can the European vision hold true in the same terms for Italy as well?